THE EFFECT OF WORK-LIFE BALANCE IMPLEMENTATION ONPRODUCTIVITY AND EMPLOYEE RETENTION IN START-UP COMPANIES - Bambang Hermawan; Didik Wahyudi (Adisam Publisher, 2025)
This study aims to analyse the effect of work-life balance implementation on employee productivity and retention in start-up companies. The background of this study is based on the high dynamics and work pressure in start-up environments, which often affect the work-life balance of employees and result in high turnover rates. The research method used is a literature review by examining various scientific sources, journals, and research reports related to work-life balance, productivity, and employee retention in start-up companies. The results of the study indicate that the implementation of work- life balance, such as flexible working hours and hybrid work systems, has a positive and significant effect on increasing employee productivity. In addition, work-life balance has also been proven to increase employee retention by reducing turnover intentions and increasing loyalty to the company. This study recommends that start-up companies continue to develop policies and programmes that support work-life balance in order to create a healthy, productive, and sustainable work environment.